2020
DOI: 10.11648/j.ajbio.20200804.11
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Evaluation of <i>Moringa oleifera, Hunteria umbellate</i> and <i>Azadirachta indica</i> with Antibiotics Against Environmental MRSA Isolates: An <i>In-vitro</i> Study

Abstract: Methicillin-Resistant Staphylococcus aureus (MRSA) is known to show resistance to beta-lactam class of antibiotics. MRSA is among the highest superbugs posing dangerous threats to humans. This study aimed at determining the in-vitro synergistic evaluation of Moringa oleifera, Hunteria umbellate and Azadirachta indica extracts with existing antibiotics (Azithromycin, Clindamycin and Vancomycin) on isolated MRSA from fomites. MRSA was isolated using the BBL™ Oxacillin agar screen test (Müller Hinton Agar with 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Several studies have shown the presence of different secondary metabolite like: alkaloids, volatile oils, tannins, flavonoids and saponins etc in the different extracts of H. umbellata [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the presence of different secondary metabolite like: alkaloids, volatile oils, tannins, flavonoids and saponins etc in the different extracts of H. umbellata [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Anibijuwon et al[37] study shows that ethanol and methanol seed extracts of H. umbellata have a zone of inhibition of 30 and 17 mm respectively against Streptococcus sp. Akinrotoye et al[28] study shows that the agar diffusion assay of H. umbellata extract-Azithromycin combination had the least zones of inhibition ≥21.00±1.92 mm in 75% of all isolates tested.…”
mentioning
confidence: 96%